Efektivitas Dan Kontribusi Pajak Kendaraan Bermotor (PKB) Terhadap Pendapatan Asli Daerah (PAD) Kabupaten/Kota Di Provinsi Bali Tahun 2019-2023 - Paramananda, I Kadek Danta; I Putu Gede Diatmika; Ni Luh Gede Erni Sulindawati (Universitas Pendidikan Ganesha, 2025)
This study aims to examine the effectiveness and contribution of Motor Vehicle Tax (PKB) in each regency/city within the Province of Bali over the five years period from 2019 to 2023. The purpose is to assess the extent to which PKB revenue met the predetermined targets and how significantly it contributed to the province’s Original Local Revenue (PAD). This research uses a descriptive quantitative approach. The data used consist of primary data obtained through interviews and secondary data in the form of reports on PKB revenue targets and realizations, as well as PAD data from 2019 to 2023. The results show that all Regionak Technical Implementation Units (UPTDs) in Bali consistently recorded effectiveness levels above 100%, indicating that actual PKB revenues exceeded the targets and reflecting optimal tax collection performance. The contribution total PKB to PAD showed annual fluctuations, with annual contributions ranging from 38% to 46%. The contribution was categorized as ‘fair’ in 2019 and 2023, and as ‘good’ from 2020 to 2022.